The Leptin System and Diet: A Mini Review of the Current Evidence - Mendoza-Herrera, Kenny; Florio, Andrea A.; Moore, Maggie; Marrero, Abrania; Tamez, Martha; Bhupathiraju, Shilpa N.; Mattei, Josiemer (Frontiers in Endocrinology, 2021)
Leptin promotes satiety and modulates energy balance and weight. Diet-induced obesity leads to leptin resistance, exacerbating overeating. We reviewed the literature on the relationship between diet and leptin, which suggests that addressing leptin resistance through dietary interventions is promising for reducing obesity. Albeit some limitations (e.g., limited rigor, small samples sizes), studies in animals and humans show that diets high in fat, carbohydrates, fructose, and sucrose, and low in protein are drivers of leptin resistance. Despite methodological heterogeneity pertaining to this body of literature, experimental studies show that energy-restricted diets can reduce leptinemia both in the short and long term and potentially reverse leptin resistance in humans. We also discuss limitations of this evidence, future lines of research, and implications for clinical and public health translations. Main limitations include the lack of a single universally-accepted definition of leptin resistance, and of adequate ways to accurately measure it in humans. The use of leptin sensitizers (drugs) and genetically individualized diets are alternatives against leptin resistance that should be further researched in humans. The tested very-low-energy intervention diets are challenging to translate into wide clinical or population recommendations. In conclusion, the link between nutritional components and leptin resistance, as well as research indicating that this condition is reversible, emphasizes the potential of diet to recover sensitivity to this hormone. A harmonized definition of leptin resistance, reliable methods to measure it, and large-scale, translational, clinical, and precision nutrition research involving rigorous methods are needed to benefit populations through these approaches.